Sturge–Weber Syndrome with Bilateral Port-Wine Stain. (15th April 2022) - Pathak, Bishnu Deep; Sharma, Shriya; Adhikari, Aakriti; Simkhada, Nabin; Ghimire, Bhuwan; Aryal, Nirjala
Abstract : Sturge–Weber syndrome is a rare congenital neurocutaneous disorder characterized by dermatological, ophthalmological, and neurological manifestations. It occurs due to abnormal persistence of embryonic vascular plexus. Here, we describe a case of four years seven months female with seizures, developmental delay, intellectual disability, and bilateral port-wine stain diagnosed as type I (classical) Sturge–Weber syndrome. The ophthalmological evaluation was unremarkable. Electroencephalogram showed abnormalities suggestive of a structural lesion in the right cerebral hemisphere. CT scan of the head revealed volume loss of right brain parenchyma with linear, cortical, as well as subcortical calcifications more evident in the right hemisphere. The child should be followed up regularly until adulthood for ophthalmological evaluation, recurrence of seizures, and other manifestations of this disorder.